The Legal Concept of the Arbitrator’s Duty of Impartiality in Arbitral Proceedings (An Analytical Study) In Light of the New Libyan Arbitration Law, General Principles, and Relevant International Conventions and Rules on Arbitration - Dr. Jamal Omran Al Mabrok (Journal of Scientific and Human Dimensions, 2026)
Commercial arbitration is considered the optimal legal means for resolving commercial disputes in general and international trade disputes in particular, due to the flexibility, speed, confidentiality, and consensual nature of this system. These features have made it the preferred method for parties engaged in global commerce to resolve disputes that may arise between them. However, the true importance of this unique system lies in the foundation of the arbitral process itself, namely the person of the commercial arbitrator. When the arbitrator is properly chosen based on experience, competence, and impartiality, the arbitration system achieves its intended purpose — issuing an arbitral award that genuinely reflects truth and justice between the disputing parties, free from bias, favoritism, or partiality toward either side.Since the commercial arbitrator acts as a judge within the scope of the arbitral dispute before him, it is essential that he maintain impartiality during the proceedings and disclose to the parties any relationships, connections, doubts, or conflicts of interest he may have with any of the disputing parties. This requirement parallels that imposed on judges in official or judicial courts, ensuring that the arbitral award remains free from the defect of partiality and thus protected from annulment, provided that such an award is not tainted by bias or favoritism.Therefore, the obligation of the commercial arbitrator to maintain legal impartiality in arbitral proceedings remains both a legal and ethical duty of great significance, deserving thorough study, analysis, and legal foundation from doctrinal, judicial, and legislative perspectives. This was the motivation behind selecting this topic as the title of the present study, which aims to provide a sound legal analysis of the issue concerning the definition, nature, and scope of the arbitrator’s duty of impartiality from doctrinal, judicial, and legislative viewpoints.The study follows a rigorous scientific methodology based on an analytical approach to all relevant legal provisions and rules governing the arbitrator’s duty of impartiality in Libyan legislation, as well as in international conventions and regulations related to commercial arbitration. The research is structured into four main sections:The first section defines the concept of the arbitrator’s impartiality doctrinally and judicially as a legal foundation of this duty. The second section identifies the characteristics of this obligation. The third section distinguishes between the concepts of impartiality, independence, and integrity from both legal scholarship and the researcher’s own perspective to ensure conceptual clarity. Finally, the fourth section examines the position of Libyan legislation, along with relevant international conventions and rules, regarding the arbitrator’s duty of impartiality in commercial arbitration.
Keywords: Arbitrator; Impartiality; Recusal